Citrus Segment Degradation Potential, Enzyme Safety Evaluation, and Whole Genome Sequence of Aspergillus aculeatus Strain ZC-1005 - Wang, Jieyi; Gao, Zhipeng; Qian, Yujiao; Hu, Xiao; Li, Gaoyang; Fu, Fuhua; Guo, Jiajing; Shan, Yang (Frontiers in Microbiology, 2021)
Aspergillus aculeatus ZC-1005 (ZC-1005 was used as the abbreviation of this strain) is a hemicellulase-producing strain isolated from rotten citrus rind buried in the soil. Our previous study has shown its biochemical properties including high xylanase activity, mannanase activity, and degradation reaction with citrus mesocarp. In this study, we focused more on the enzyme safety evaluation and the genome sequencing via PacBio and Illumina platforms. High biological safety of the crude enzymes of ZC-1005 has been proved by acute oral toxicity test, sub-chronic toxicity test, micronucleus test and sperm malformation test. The genome of ZC-1005 had a GC content of 52.53%, with a size of 35,458,484 bp, and encoded 10147 genes. Strain ZC-1005 harbored 269 glycosyl hydrolase (GH) genes of 64 families. The fungus produces cellulose-acting (GH 3, 5, 12, and 1) and hemicellulose-acting enzymes (GH 16, 31, 2 and 92). In genome annotation, we paid more attention to the genes encoding xylanase, such as gene 01512, gene 05833, gene 05469, gene 07781, gene 08432, gene 09042, gene 08008 and gene 09694. The collaboration between complete genome information and the degradation test confirmed that ZC-1005 could degrade cellulose and xylan. Our results showed that the citrus enzymatic decapsulation technology was efficacy and safe for canned citrus products processing, which may also solve the industrial waste problems. Therefore, ZC-1005 and the crude enzyme secreted from the strain were very promising to be used in the citrus processing industry.